The Dynamics of Reservation Wages: Preliminary Evidence from the GSOEP - Enswar Prasad (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper presents preliminary results from an empirical analysis of the individual and macroeconomic deter-minants of reservation wages, using data from the German Socio-Economic Panel. The longitudinal aspect of the dataset provides an interesting perspective on the dynamics of reservation wages and their correlations with accepted wage offers for workers who make the transition from unemployment to employment. The findings have important policy implications as well, since they shed some light on the disincentive effects of the German tax and transfer system for the labor supply and employment decisions of unemployed workers at different points of the skill/offer wage distribution.
Keywords: 330; Arbeitsangebot; Lohn; Arbeitslosigkeit; Lohnstruktur; Anspruchslohn; Bildungsertrag; Qualifikation; Deutschland